The interaction between thyroid and kidney disease: an overview of the evidence. Issue 5 (October 2016) - Rhee, Connie M.
Abstract : Purpose of review: Hypothyroidism is highly prevalent in chronic kidney disease (CKD) patients, including those receiving dialysis. This review examines potential mechanistic links between thyroid and kidney disease; current evidence for hypothyroidism as a risk factor for de novo CKD and CKD progression; and studies of thyroid functional disorders, cardiovascular disease, and death in the CKD population. Recent findings: Epidemiologic data have demonstrated an incrementally higher prevalence of hypothyroidism with increasing severity of kidney dysfunction. Various thyroid functional test abnormalities are also commonly observed in CKD due to alterations in thyroid hormone synthesis, metabolism, and regulation. Although the mechanistic link between thyroid and kidney disease remains unclear, observational studies suggest that hypothyroidism is associated with abnormal kidney structure and function. Previously thought to be a physiologic adaptation, recent studies show that hypothyroidism is associated with higher risk of cardiovascular disease and death in CKD. Summary: A growing body of evidence suggests that hypothyroidism is a risk factor for incident CKD, CKD progression, and higher death risk in kidney disease patients. Rigorous studies are needed to determine the impact of thyroid hormone replacement upon kidney disease progression, cardiovascular disease, and mortality, which may shed light onto the causal implications of hypothyroidism in CKD.